Pemahaman Vaksinasi Pada Masyarakat di Jakarta - Gunawan Widjaja (Adiba Aisha Amira, 2022)
People whounderstand the needsin their lives, will immediately find out everything about vaccination, because if they do not concernabout the importance of being vaccinated, they will always have poor knowledge and will have the potential to refuse to be vaccinated. As described by the researchers in this paper, it is known that until now only 7% of people have a negative understanding of this vaccination, who reject it. Besides medical personnel or the relevant government officials always educate the importance of vaccination in orderto have strong antibodies and avoid various kinds of infectionfrom theviruses that attack the human body.